Transactional innovation and the de-commoditization of the Brazilian coffee trade - Pierpaolo Andriani; Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2011)
Recent research into international trade has highlighted the role of trade costs in determining the geography of trade. We propose that the notion of comparative advantage has to be expanded to include different capacities to transact and the pertinent factor endowments (organizational and social capital). In a 'transactional regime', sets of transaction-enabling tasks (TETs) are arranged to overcome a given pattern of trade resistances. We argue that transactional regimes impact the flows and contents of information that guide the decision making of producers and therefore also shape the resulting international division of labour. Transactional regimes can be classified according to a three-dimensional state space of trade resistances covering certain most generic aspects of information. We apply this approach to analyze the case of the Brazilian coffee business that has evolved into a bifurcated 'commoditized' and 'de-commoditized' regime in the past twenty years, triggered by the entrepreneurial action of a single company, illycaffè. An entirely new business model has resulted into a shift of the transactional regime in coffee trade, with implications for the distribution of the gains from trade.
Keywords: F14; F19; 330; trade costs; trade in tasks; transactional regime; entrepreneurship in international trade; coffee; illycaffè